Pulmonary hypertension in Finland 2008-2020: A descriptive real-world cohort study (FINPAH) - Markku Pentikäinen; Piia Simonen; Helena Tuunanen; Pauliina Leskelä; Terttu Harju; Pertti Jääskeläinen; Christian Asseburg; Minna Oksanen; Erkki Soini; Christina Wennerström; Airi Puhakka; Terttu Harju; et al. (JHLT Open, 2025)
Background: To assess characteristics, risk group distribution, and prognosis of patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH) in Finland. Methods: Clinical chart review of patients with PAH or CTEPH recorded between 2008 and 2019 and linkage to official mortality data. Results: We identified 627 patients, with 502 (80%) diagnosed after 2008, yielding an incidence of PAH and CTEPH of 4.0 and 2.9/million/year, respectively. The median time from symptoms to diagnosis was 1 year. Mean age at diagnosis of PAH patients (n = 268) was 57 years, 73% were women, 40% had idiopathic PAH, 28% associated with connective tissue diseases, and 15% with congenital heart disease, 9% had ≥3 cardiovascular comorbidities. At 1 year, 34%/34%/24%/8% were at the low/intermediate-low/intermediate-high/high Compera 2.0 risk classification groups. Survival was 91.3%, 74.8%, and 62.6% at 1, 3, and 5 years, respectively, with an improving trend over calendar time. Ten PAH patients had a lung transplant. PAH subtype, cardiac output, and the presence of ischemic heart disease or type 2 diabetes predicted survival.CTEPH patients (n = 189) were 63 years (mean) at diagnosis and 49% were women. Of the CTEPH patients, 29% underwent pulmonary endarterectomy (PEA) and 22% were treated with balloon pulmonary angioplasty. Survival was 94.6%, 87.2%, and 79.4% at 1, 3, and 5 years, respectively. PEA patients were younger, had fewer comorbidities, and had longer survival than non-PEA patients. Conclusions: Incidence and survival of PAH and CTEPH patients in Finland were similar to previously presented data for other countries.